Assessment of neonatal care in clinical training facilities in Kenya. Issue 1 (19th August 2014) - Aluvaala, Jalemba; Nyamai, Rachael; Were, Fred; Wasunna, Aggrey; Kosgei, Rose; Karumbi, Jamlick; Gathara, David; English, Mike
Abstract : Objective: An audit of neonatal care services provided by clinical training centres was undertaken to identify areas requiring improvement as part of wider efforts to improve newborn survival in Kenya. Design: Cross-sectional study using indicators based on prior work in Kenya. Statistical analyses were descriptive with adjustment for clustering of data. Setting: Neonatal units of 22 public hospitals. Patients: Neonates aged <7 days. Main outcome measures: Quality of care was assessed in terms of availability of basic resources (principally equipment and drugs) and audit of case records for documentation of patient assessment and treatment at admission. Results: All hospitals had oxygen, 19/22 had resuscitation and phototherapy equipment, but some key resources were missing—for example kangaroo care was available in 14/22. Out of 1249 records, 56.9% (95% CI 36.2% to 77.6%) had a standard neonatal admission form. A median score of 0 out of 3 for symptoms of severe illness (IQR 0–3) and a median score of 6 out of 8 for signs of severe illness (IQR 4–7) were documented. Maternal HIV status was documented in 674/1249 (54%, 95% CI 41.9% to 66.1%) cases. Drug doses exceeded recommendations by >20% in prescriptions for penicillin (11.6%, 95% CI 3.4% to 32.8%) and gentamicin (18.5%, 95% CI 13.4% to 25%), respectively. Conclusions: Basic resources are generally available, but there are deficiencies in key areas. Poor documentation limits the use of routine data for quality improvement. Significant opportunities exist for improvement in service delivery and adherence to guidelines in hospitals providing professional training.